2013
DOI: 10.1159/000350127
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Maintains Late-Stage Functional Cardiomyocytes in Embryoid Bodies Derived from Murine Embryonic Stem Cells

Abstract: Background/Aims: Low efficiency of cardiomyocyte (CM) differentiation from embryonic stem (ES) cells limits their therapeutic use. The objective of this study was to investigate the effect of baicalin, a natural flavonoid compound, on the in vitro cardiac differentiation of murine ES cells. Methods: The induction of ES cells into cardiac-like cells was performed by embryoid body (EB)-based differentiation method. The electrophysiological properties of the ES cell-derived CMs (ES-CMs) were measured by patch-cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…The mES cell line D3 (ATCC, USA) and its transgenic cell line αPIG (clone 44) were cultured and differentiated into spontaneously beating CMs as previously described [3]. Briefly, the embryoid bodies (EBs) were generated using the hanging drop method in Iscove's Modified Dulbecco's Medium supplemented with 20 % fetal bovine serum, 1 % non-essential amino acids, 2 mM L-glutamine, 100 units/mL penicillin-streptomycin, and 0.1 mM β-mercaptoethanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mES cell line D3 (ATCC, USA) and its transgenic cell line αPIG (clone 44) were cultured and differentiated into spontaneously beating CMs as previously described [3]. Briefly, the embryoid bodies (EBs) were generated using the hanging drop method in Iscove's Modified Dulbecco's Medium supplemented with 20 % fetal bovine serum, 1 % non-essential amino acids, 2 mM L-glutamine, 100 units/mL penicillin-streptomycin, and 0.1 mM β-mercaptoethanol.…”
Section: Methodsmentioning
confidence: 99%
“…This strategy is transplanting suitable cells into the infarcted area of heart which can functionally integrate into the host tissue, and thus rescuing cardiac function [1]. Embryonic stem (ES) cells generated from blastocysts inner cell mass can differentiate into beating cardiomyocytes (CMs) in vitro , which have been widely accepted as a promising source for cell replacement therapy [1,2,3,4]. The typical structure of adult CMs is characterized by bundles of parallel myofilaments, sarcomeres with Z-disc, A-, I-, and H-band as well as the M-line, which are the structural basis of cardiac muscle contraction.…”
Section: Introductionmentioning
confidence: 99%
“…The differentiation of ES cells was induced by the generation of embryoid bodies (EBs) using the hanging drop method as previously described [11] with differentiation culture medium composed of Iscove's modified Dulbecco's medium (GIBCO), 20% FBS, 0.1 mmol/L β-mercaptoethanol, 1% NEAA, 2 mmol/L L-glutamine, 100 units/mL penicillin-streptomycin. Puerarin (1 µmol/L, 10 µmol/L, 100 µmol/L, 1000 µmol/L, Drug Biology Product Examination Bureau, Beijing, China) was added from day 0 to day 16.…”
Section: Methodsmentioning
confidence: 99%
“…So far, proteins from TGFβ, BMP, and Wnt families [4,5,6], cytokines [7], natural or synthetic chemical compounds [3,8,9,10,11]; and several transgenic ES cell systems [12] have been applied to selectively enhance the efficiency of cardiac differentiation from ES cells. Among these reports, retinoic acid and transgenic ES cell system are highlighted by their effects on ventricular specialization of ES cells.…”
Section: Introductionmentioning
confidence: 99%
“…These active components regulate either the transcription factors [13] or the cell cycle-related genes thereby affecting stem cell differentiation, proliferation and apoptosis. Our previous data have revealed that TCMs baicalin, puerarin and ginsenoside Rg1 influence the cardiac differentiation of mESCs [14,15,16] by changing the expression of the cardiac-specific transcriptional factors. Whether they could also exert effects on mESCs proliferation by modifying the expression of mESC-miRNAs remains to be determined.…”
Section: Introductionmentioning
confidence: 99%